2022
DOI: 10.1002/cbdv.202200644
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity and Cell Imaging of Antitumor Fluorescent Agents (Curcumin Derivatives) Coated by Two‐Way Embedded Cyclodextrin Strategy

Abstract: Curcumin has a wide range of pharmacological activities, which can be used to treat tumors, inflammation and other diseases. However, curcumin's poor solubility and low bioavailability limit its application. In this article, the structure of curcumin was modified with boron trifluoride ether to change fluorescent labeling. The compounds were then embedded into the hydrophobic cavity of α‐cyclodextrin and hydroxypropyl β‐cyclodextrin to form inclusion complexes. The two inclusion complexes have excellent photop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 32 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…The important characteristic and active components extracted from the traditional chinese medicine turmeric have good application prospects and clinical therapeutic potential in the diversity of pharmacological actions ( Kocaadam and Sanlier 2017 ; Hosseini and Hosseinzadeh 2018 ; Hay et al, 2019 ; Liu et al, 2022a ). In a number of studies involving cancer and tumor cells, it was found that curcumin may play a good inhibitory role in a variety of different links ( Mortezaee et al, 2019 ; Zendehdel et al, 2019 ), it effectively inhibits the uncontrolled metastasis of cancer cells ( Jia et al, 2019 ), the proliferation of tumor cells, the activity of cancer-inducing chemicals in the stomach and colon ( Porras et al, 2020 ; Naji et al, 2021 ), and inhibits angiogenesis by modulating protease activity ( Binion et al, 2008 ; Liu et al, 2022b ; Hu et al, 2022 ). However, curcumin has some disadvantages such as poor water solubility, low bioavailability and poor gastrointestinal absorption ( Sabet et al, 2021 ; Sohn et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The important characteristic and active components extracted from the traditional chinese medicine turmeric have good application prospects and clinical therapeutic potential in the diversity of pharmacological actions ( Kocaadam and Sanlier 2017 ; Hosseini and Hosseinzadeh 2018 ; Hay et al, 2019 ; Liu et al, 2022a ). In a number of studies involving cancer and tumor cells, it was found that curcumin may play a good inhibitory role in a variety of different links ( Mortezaee et al, 2019 ; Zendehdel et al, 2019 ), it effectively inhibits the uncontrolled metastasis of cancer cells ( Jia et al, 2019 ), the proliferation of tumor cells, the activity of cancer-inducing chemicals in the stomach and colon ( Porras et al, 2020 ; Naji et al, 2021 ), and inhibits angiogenesis by modulating protease activity ( Binion et al, 2008 ; Liu et al, 2022b ; Hu et al, 2022 ). However, curcumin has some disadvantages such as poor water solubility, low bioavailability and poor gastrointestinal absorption ( Sabet et al, 2021 ; Sohn et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Drugs with limited solubility may become more soluble by coating technology, improving their relative bioavailability in the body and allowing for improved absorption. Additionally, acrylic resin has the benefit of having less hazardous side effects and minimizing bodily harm ( Liu et al, 2022b ; Ying et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%